MATHEMATICAL TOOLING OF ESTIMATION OF ECONOMIC EFFICIENCY OF AGRICULTURAL TRACTORS - V. B. Samorodov; O. G. Kryvokon (Фінансово-кредитна діяльність: проблеми теорії та практики, 2019)
Work is sanctified to introduction of complex comparative estimation of economic efficiency of agricultural tractors. It is set that to present tense the absent is generalized complex index, that is able to estimate economic efficiency of work of machine- tractor aggregates (МТА), index, that not only grounds the rational choice of type of МТА but also provides the minimum constituent of running expenses on treatment of earth in an eventual agricultural unit cost at the market. Experience of creation on Ukraine of new tractors (tractors of ХТЗ-21021, ХТЗ-242К with HVMT) first on post-soviet space at the Kharkiv tractor plant resulted in the necessity of development of mathematical tool of design and prognostication of comparative estimation of economic efficiency of МТА on their base. An offer algorithm first allows to set new intercommunications between basic technical and economic parameters and estimation of economic efficiency of tractor (in measuring of losses a hryvnya is on the hectare of treatment of area). The worked out mathematical tool of design of estimation of economic efficiency is first tested in the format of numeral experiment for tractors with application of HVMT as ГОМТ-1С and ГОМТ-2С, worked out on the department of department of "Cars and tractors" of National Technical University "Kharkov polytechnic institute" (NTU "KhPI") for the tractors of ХТЗ-21021 and ХТЗ-242К for " Kharkov tractor plant". Is got all spectrum of kinematics, power, power descriptions of HVMT and basic technical and economic parameters on the whole machine- tractor aggregate, the width of capture of plough is optimized on the criterion of maximal output-input of HVMT ratio, the value of the productivity is found at most, minimum per hectare expense of fuel, minimum losses in hryvnyas on treatment tractor 1 hectare area. The presented mathematical tool allows in the format of numeral experiment to compare efficiency of the wheeled tractors both step hydraulic-mechanical transmissions work in composition that and of HVMT. The brought mathematical tooling over allows to get the comparative estimation of economic efficiency of different home and foreign tractors.